Anti-glare film, and optical member and liquid crystal display apparatus using the same - TAKAHASHI HIROSHI; USHIDA HIROAKI (2005)
An anti-glare film comprising an anti-glare layer is obtained by coating or casting a liquid composition containing a polymer, a curable resin precursor (e.g., an ultraviolet curable resin) and a solvent, on a transparent plastic film; evaporating the solvent; forming a phase separation structure by spinodal decomposition; and curing the curable resin precursor by a light irradiation to form the anti-glare layer. The result anti-glare layer has an uneven structure on the surface thereof, isotropically transmits and scatters an incident light to show the maximum value of the scattered light intensity at a scattering angle of 0.1 to 10°, and has the total light transmittance of 70 to 100%.